SISTEM PAKAR UNTUK DETEKSI PENYAKIT PADA AYAM - Irianto, Suhendro Yusuf; Sari, Dian (Jurnal Informatika, 2011)
In this paper we try explore artificial intelligent approach to detect poultry desease caused by virus. We built a web based expert system application to help veterinarian diagnose poultry whether infected by virus or not. In this work we utilize expert system to decide what kind of virus or desesase detected. Our work demonstrates that our expert system algorithm quite good eventhough the menu structure is quite simple. Application was built with PHP on windows platform since PHP considered as widely used tool for developing web technology programming. The system has also some advantages such as fast, eliminate data redundant, and accurate in deciding kid of virus detected. Keywords : artificial intelligent, virus, poultry.